Design, Physicochemical Characterization, and In Vitro Permeation of Innovative Resatorvid Topical Formulations for Targeted Skin Drug Delivery - Victor H. Ruiz; David Encinas-Basurto; Bo Sun; Basanth Babu Eedara; Sally E. Dickinson; Georg T. Wondrak; H. -H. Sherry Chow; Clara Curiel-Lewandrowski; Heidi M. Mansour (MDPI AG, 2022)
Nonmelanoma skin cancers (NMSCs) are the most common malignancies worldwide and affect more than 5 million people in the United States every year. NMSC is directly linked to the excessive exposure of the skin to solar ultraviolet (UV) rays. The toll-like receptor 4 (TLR4) antagonist, resatorvid (TAK-242), is a novel prototype chemo preventive agent that suppresses the production of inflammation mediators induced by UV exposure. This study aimed to design and develop TAK-242 into topical formulations using FDA-approved excipients, including DermaBaseTM, PENcreamTM, polyethylene glycol (PEG)-400, propylene glycol (PG), carbomer gel, hyaluronic acid (HA) gel, and Pluronic® F-127 poloxamer triblock copolymer gel for the prevention of skin cancer. The physicochemical properties of raw TAK-242, which influence the compatibility and solubility in the selected base materials, were confirmed using X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC), hot-stage microscopy (HSM), Raman spectroscopy, and attenuated total reflectance Fourier-transform infrared (ATR-FTIR) spectroscopic analysis. The permeation behavior of TAK-242 from the prepared formulations was determined using Strat-M® transdermal diffusion membranes, and 3D cultured primary human-derived epidermal keratinocytes (EpiDermTM). Despite TAK-242's high molecular weight and hydrophobicity, it can permeate through reconstructed human epidermis from all formulations. The findings, reported for the first time in this study, emphasize the capabilities of the topical application of TAK-242 via these multiple innovative topical drug delivery formulation platforms.